Structural, mechanical and electrical characterization of epoxy-amine/carbon black nanonocomposites (eXPRESS Polymer Letters, 2008)
This work presents an insight into the effect of preparation procedure and the filler content on both electrical and mechanical properties of a nanocomposite system. For the preparation of the nanocomposites diglycidyl ether of bisphenol A (DGEBA) was used with triethylenetetramine (TETA) as a curing agent. As fillers carbon black (CB) nanoparticles with size from 25 to 75 nm were used. The characterization was done using Dynamic Mechanical Analysis (DMA), Dielectric Relaxation Spectroscopy (DRS), Differential Scanning Calorimetry (DSC), Wide Angle X-ray Diffraction (WAXD) and electrical conductivity measurements. The dependence of the dynamic mechanical and dielectric parameters (E′, E″, tanδ, ε', ε″, σ and Tg) is associated with the filler content and is controlled by the employed curing conditions. An increase in electrical conductivity, which is observed at about 1% w/w of carbon black, indicates the creation of conducting paths and is associated with the Maxwell Wagner Sillars (MWS) relaxation, probably due to the formation of aggregated microstructures in the bulk composite..